Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $x_0,...,x_n$ be distinct real numbers and $l_k(x)$ be the Lagrange's basis function. $\delta_n = \prod^n_{k=0}(x-x_k)$.

Prove that:

a. - $\sum^n_{k=0}(x_k-x)^jl_k(x)\equiv 0$, for $j = 0,1,...,n$

b. - Let $p(x)$ be any polynomial of degree $n+1$ with its highest degree coefficient $a_{n+1} =1$. Then, $p(x) - \sum^n_{k=0}p(x_k)l_k(x) = \delta_n(x)$

a. - I know that Lagrange functions $l_k(x)$ there are k terms in the product where each term contains an $x$ but then how does multiplying it by $(x_k-x)^j$ make it equivalent to $0$?

b. - I do not know how to do the proof. I tried googling it and found "Lagrange's fundamental interpolating polynomials" which seems similar to it.

share|cite|improve this question
up vote 2 down vote accepted

(The Lagrange basis functions are $$ l_k(x):=\frac{\prod_{0\le i\le n,\ i\ne k} (x - x_i)}{\prod_{0\le i\le n, \ i\ne k} (x_k - x_i)}, \qquad k=0,\dots,n.) $$

(a) This is not true for $j=0$, but it works for $j=1$, $\dots$, $n$.

For any polynomial $f(x)$, let $${\overline{f(x)}}:=\sum_{0\le k\le n} f(x_k) l_k(x).$$ Then $\deg {\overline{f(x)}}\le n$ and $f(x)$ and ${\overline{f(x)}}$ agree at $x=x_0$, $\dots$, $x=x_n$. Since a nonzero polynomial of degree $n$ or less can have at most $n$ zeroes, it follows that, if $\deg f(x)\le n$, ${\overline{f(x)}}=f(x)$.

Now, in the sum in (a), replace the first $x$ by $y$ to give \begin{eqnarray*} \sum_{0\le k\le n} (x_k-y)^j l_k(x). \end{eqnarray*} Treat this as a polynomial in $x$ with coefficients which are functions of $y$. Then, it is ${\overline{(x-y)^j}}$. But $j\le n$, so by the last paragraph, this equals $(x-y)^j$. Substituting the $x$ back in gives $(x-x)^j=0$.

(b) This can be rewritten as $$ p(x)-{\overline{p(x)}} = \delta_n(x).\ \ \ \ (*) $$ By the above, since $\deg (p(x)-\delta_n(x))\le n$, $$ p(x)-\delta_n(x) = {\overline{p(x)- \delta_n(x)}}. \ \ \ \ (**) $$ But since $\delta_n(x_0)=\dots=\delta_n(x_n)=0$, ${\overline{p(x)-\delta_n(x)}}=\overline{p(x)}$. Substituting this into (**) gives (*).

share|cite|improve this answer
Thanks David Moews! – user60514 Feb 1 '13 at 20:41
In part (a), is y a variable? or a function that depends on x? or is it some sort of placeholder that we eventually replace with x? – tylerc0816 Feb 3 '13 at 3:18
It's a variable. – David Moews Feb 3 '13 at 20:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.